Production Scheduling in the Process Industries: Current Trends, Emerging Challenges and Opportunities - Henning, Gabriela Patricia (2009)
This paper discusses the current trends and defies associated with productionscheduling, both from an industrial and academic perspective. First, the new challengesthat appear in the context of globalized and competitive economies are addressed. Theystem from the need of considering scheduling as a building block of the AdvancedPlanning Systems (APSs) that nowadays participate in Supply Chain Management(SCM) functions. They are primarily associated with business process coordination andinformation integration requirements. Then, main features, strengths and limitations ofcurrent academic proposals are briefly addressed. Finally, some of the reasons for theslow acceptance and modest penetration of these research results are highlighted. Thus,challenges and opportunities to be faced in order to alleviate the miscommunication ofthe academic and industrial worlds are pointed out.